Deoxycholic Acid and Lithocholic Acid Alleviate Liver Injury and Inflammation in Mice with Klebsiella pneumoniae-Induced Liver Abscess and Bacteremia - Zheng Y; Yue C; Zhang H; Chen H; Liu Y; Li J (Dove Medical Press, 2021)
Yahong Zheng,1 Chengcheng Yue,1 Hui Zhang,1 Haoran Chen,1 Yanyan Liu,1 Jiabin Li1– 4 1Department of Infectious Diseases, The First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2Department of Infectious Diseases, The Chaohu Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 3Anhui Center for Surveillance of Bacterial Resistance, Hefei, People’s Republic of China; 4Institute of Bacterial Resistance, Anhui Medical University, Hefei, People’s Republic of ChinaCorrespondence: Jiabin LiDepartment of Infectious Diseases, The First Affiliated Hospital of Anhui Medical University, Jixi Road No. 218, Hefei, 230022, People’s Republic of ChinaTel +86-551-62922713Fax +86-551-62922281Email lijiabin@ahmu.edu.cnPurpose: Klebsiella pneumoniae-induced liver abscess and baiacterem is a serious infectious disease with high mortality. Secondary bile acids (SBAs) are produced by intestinal flora through the metabolism of primary bile acids and play a role in promoting or inhibiting inflammation in some diseases. However, the immunomodulatory role of SBAs in bacterial infections of the liver remains unclear. This study aimed to investigate the anti-inflammatory and liver-protective effects of SBAs in K. pneumoniae-infected mice.Methods: The absolute concentrations of deoxycholic acid (DCA) and lithocholic acid (LCA) in feces and serum were analyzed, and intestinal flora alterations between K. pneumoniae-infected and healthy control mice were examined. The effect of SBAs was investigated by analyzing the survival, tissue bacterial load, histopathology, and inflammatory factor levels in SBA-treated mice. The expression of crucial proteins implicated in the NF-κB pathway, as well as the G-protein-coupled bile acid receptor TGR5, was detected.Results: The content of SBAs in feces and serum of the K. pneumoniae-infected group was significantly reduced, and significant changes in the composition of the intestinal flora were detected. The intestinal flora are directly related to the synthesis of SBAs. Ruminococcaceae levels in K. pneumoniae-infected mice were significantly lower than in healthy control mice. Oral administration of SBAs improved the survival and liver pathology of K. pneumoniae-infected mice, and reduced the bacterial load and the level of inflammatory factors. SBAs down-regulated the expression of key proteins in the NF-κB inflammatory signaling pathway, including the phosphorylation of IκBα and NF-κB p50 and the nuclear translocation of NF-κB p65. The protective effect of SBAs may be dependent on high TGR5 expression.Conclusion: SBAs downregulate the NF-κB inflammatory signaling pathway through TGR5, protecting the liver and inhibiting inflammation in K. pneumoniae-induced liver abscess and bacteremia.Keywords: Klebsiella pneumoniae liver abscess, deoxycholic acid, lithocholic acid, inflammation, nuclear factor-κB